Acute ischemic stroke treatment model for Poland in the mechanical thrombectomy era – which way to go? - Pawłowski, Krzysztof; Dziadkiewicz, Artur; Klaudel, Jacek; Mączkowiak, Alicja; Szołkiewicz, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
The interventional treatment of acute ischemic stroke with large vessel occlusion has revolutionized patient care in recent years. The Mechanical Thrombectomy Pilot Program in Poland is due to end soon. It seems the right time to summarize the achievements and name the problems of a centralized stroke care system and decide what future model of treatment and transportation to implement. In order to provide the best care for our patients, it is crucial to establish the actual needs in stroke and tailor the mechanical thrombectomy system structure accordingly. The analysis of data from well-organized health systems in the world suggests that to deliver adequate numbers of mechanical thrombectomy to stroke patients in Poland, we would need to at least double the number of procedures currently performed. To achieve this, an essential system reorganization and adjustments are required, with special emphasis on the number of mechanical thrombectomy centers and transportation models. The strengths and weaknesses of two dominant transportation models (mothership and drip-and-ship) are herein discussed, and a proposal on how to build an efficient and cost-effective mechanical thrombectomy stroke network in Poland is put forward. The article is an invitation to open an interdisciplinary discussion on the best treatment model of acute ischemic stroke patients requiring mechanical thrombectomy in Poland.